2016
DOI: 10.1039/c6cc05496j
|View full text |Cite
|
Sign up to set email alerts
|

CeO2 nanorods anchored on mesoporous carbon as an efficient catalyst for imine synthesis

Abstract: CeO nanorods anchored on mesoporous carbon exhibit high activity and stability in aerobic oxidative coupling of alcohols and amines to imines. The abundant surface Ce and the suitable interaction between CeO nanorods and the carbon support should be responsible for the excellent catalytic behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…They are (1) the direct coupling of alcohols and amines under aerobic or anaerobic condition and the by‐products are water and hydrogen, (2) oxidation of primary amines to imines through NH‐imine intermediate and (3) the oxidative dehydrogenation of secondary amines . The direct coupling of alcohols and amines was catalyzed by various noble (Ru,, Pd,, Au, and Rh) as well as non‐noble metals (Co, Fe and Cu) under air or inert atmosphere, and heterogeneous catalysts were also reported. The catalysts promote direct dehydrogenation of alcohols followed by coupling.…”
Section: Introductionmentioning
confidence: 99%
“…They are (1) the direct coupling of alcohols and amines under aerobic or anaerobic condition and the by‐products are water and hydrogen, (2) oxidation of primary amines to imines through NH‐imine intermediate and (3) the oxidative dehydrogenation of secondary amines . The direct coupling of alcohols and amines was catalyzed by various noble (Ru,, Pd,, Au, and Rh) as well as non‐noble metals (Co, Fe and Cu) under air or inert atmosphere, and heterogeneous catalysts were also reported. The catalysts promote direct dehydrogenation of alcohols followed by coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Other organic reactions can benefit from tailoring acid/base redox properties through the modification of ceria shapes. Thus, the coupling of redox ability with the presence of weak acid sites can explain the higher activity of nanorods in the aerobic oxidative coupling of alcohols and amines to imines [155][156] . Similarly, the presence of medium strength Lewis acid sites on ceria is responsible for its activity in hydrolysis reactions under liquid phase 157 ; here the {111} crystalline facet was more active than the {110}…”
Section: Catalytic Behavior Oxidation Reactionmentioning
confidence: 99%
“…Zhang et al. anchored CeO 2 nanorods onto MC, and claimed that the observed high activity and stability can be attributed to both abundant surface Ce 3+ and the suitable interactions between CeO 2 and MC . While previous studies have shown attractive potentials of heterogeneous catalysts for imine syntheses, estimated values of turnover frequency (TOF), an important performance parameter directly determining the productivity of unit active site, are typically limited to less than 1.0 h −1 , not sufficient for practical large‐scale applications.…”
Section: Introductionmentioning
confidence: 96%
“…However, large‐scale applications of homogeneous catalysts are restricted by their inability to be recycled and the pure oxygen oxidant that may result from the high separation and equipment input. To circumvent such problems, many solid catalysts including manganese octahedral molecular sieve (OMS‐2), CeO 2 , MnCo 2 O 4 and CeO 2 /mesoporous carbon (MC) have been developed and examined for the heterogeneous catalysis of the condensation reaction . Promisingly, most of these heterogeneous catalysts allows for the use of oxygen diluted in air as an efficient oxidant during the syntheses of imines.…”
Section: Introductionmentioning
confidence: 99%